Cataclysmic variable stars: Photometry of V893 Sco star and spectroscopy of HS 0220 + 0603 star - Cori W. (2018)
Differential photometry was applied on V893 Sco star, observed from the Astronomical Observatory of the Universidad Nacional de Ingeniería in Peru. From its light curve it was measured an orbital period of 0.076 days approximately. Moreover, spectroscopic analysis was performed on the HS 0220 + 0603 star, which data was acquired from a database. A fitting program was written in Python to find, out of several synthetic spectra of white dwarf and templates of red dwarf, the combination of a white dwarf and a red dwarf spectrum that fits best the HS 0220 + 0603 spectrum, thus we found that this spectrum is a composition of a white dwarf spectrum of 30000 K and surface gravity (log g) = 8.0, and a M5.5 type red dwarf star.